Penerapan Ajaran Tri Hita Karana Dalam Penyusunan Awig-Awig Sekaa Teruna Taman Sari Di Banjar Lantang Bejuh Desa Adat Sesetan - I Nyoman Alit Putrawan; I Made Adi Widnyana; I Made Suastika Ekasana; Desyanti Suka Asih K.Tus; I Gusti Ayu Jatiana Manik Vedanti (Jayapangus Press, 2021)
Customary law in Bali is a basis or guideline in carrying out rights and obligations in an indigenous organization, including Sekaa Teruna. The form of customary law in Bali is Awig-Awig, in terms of the preparation of Awig-Awig the concept of wisdom in the community is often adopted as part of the existing peculiarities. The purpose of this writing is for to show that the concept of Tri Hita Karana is able to be synergized in the process of preparing Awig-Awig and become an important part in explaining the relationship of rights and obligations krama. From the study carried out the concept of customary legal order dibali exist in various forms such as awig, awig, perarem, eka eli kita, and others. The concept of Tri Hita Karana is often used in linking the rights and obligations of Sekaa members in the fields of parhyangan, pawongan and palemahan. In the preparation of Awig-Awig Sekaa Teruna Taman Sari is carried out synergy by using Tri Hita Karana as a foothold in describing self-sufficiency in three areas of life.